(3OjhGf MSjf fLa GdcHjQ (B((3aj eOM Cgd GdHjJ(B)s - (3CHhGdLhGO MSjf Hf eMeO Hf fLa Ydj GdJHQjRj,J (B1251 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3bGd QVj Gddg Yfg jeOM CejQ GdeDefjf YdjkG UdhGJ Gddg Ydjg hjJXde dg(B: (3dYdj efGbH dG JVGgi dG fHj hdG hUj MhGgG s
(3BNQgG (B:s
(3EPG bGd(B: (3PG ddfGQ Sge hPGc dj aVeJ Ydi GdCZOGA Ohf Jegd hSjbJ Edi NdO GdLfGf ShGgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B65s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B85 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(633) s
Keywords: (3GdCOHs